Experimental investigation of the effect of steel fibers on mechanical and impact strength of self-compacting composite slabs - Ahmad Dalvand (Iranian Society of Structrual Engineering (ISSE), 2021)
The use of self-compacting high performance composites due to its unique properties has attracted the attention of researchers.The high compressive strength and tensile strength, high flexural strength, have attracted the attention of researchers to this type of cement composites.In this research, in the form of a comprehensive experimental work, using six basic mixing designs, 24 rectangular composite slabs 300 to 400 mm, with two thicknesses of 30 and 50 mm, were built and tested under impact load. Compressive,tensile and flexural strength tests were made on each of the six mixing designs. Also, to determine the efficacy of high performance composite, slump flow, L-box, U-box and V-funnel on mix designs have been done. Steel fibers with percentages of 0, 0.5 and 1% by volume fraction, with lengths of 25 and 50 mm, were used for the construction of cementitious composites. The impact test apparatus was made from a 5.6 kilogram steel ball and a retaining system. The steel ball was raised to a height of 1.5 meters and was freed repeatedly until failure cracking in the samples have been Developed. According to the results of the experiment, It was noted that the maximum energy absorption in a slab with a thickness of 30 mm was 34.22 kJ, and in a slab with a thickness of 50 mm was 47.49 kJ. The results of this experiment shows the high effect of steel fibers on increasing the impact resistance and absorbed energy of the composite slabs.